Genotoxicity - A Predictable Risk to Our Actual World 2018
DOI: 10.5772/intechopen.74128
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity by Electromagnetic Fields

Abstract: Modern life implies a constant exposure of living organisms to many sources of radiation, especially electromagnetic fields (EMFs) generated by our technological devices. The question of whether or not EMFs in the non-ionizing extremely low frequency (ELF) range can induce genotoxic effects is currently a subject of interest. People of industrialized societies are commonly exposed to EMFs and waves in a very broad range of frequencies, including power lines, telecommunications, and domestic and industrial equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Some investigators demonstrated that by transferring drug (e.g., amphotericin B and metronidazole) information to water molecules by means of resonant circuit coupled to electronic amplifier (bioresonance therapy device, Bicom), the growth of candida and amoeba was remarkably inhibited. They suggested that it is possible to store and transfer biological information to distilled water, and that water samples subjected to such information transfer, could successfully interact with other biological systems (21,22). In living organisms, most of the biological information is transferred via a carrier like water mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators demonstrated that by transferring drug (e.g., amphotericin B and metronidazole) information to water molecules by means of resonant circuit coupled to electronic amplifier (bioresonance therapy device, Bicom), the growth of candida and amoeba was remarkably inhibited. They suggested that it is possible to store and transfer biological information to distilled water, and that water samples subjected to such information transfer, could successfully interact with other biological systems (21,22). In living organisms, most of the biological information is transferred via a carrier like water mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the characteristic frequency of insulin exerting the hypoglycemic effect is identified, patients with diabetes mellitus could be treated without insulin injection. In some studies (13,21,22), water was used as information carrier, while electromagnetic waves were used in the current study.…”
Section: Discussionmentioning
confidence: 99%